Patient Reported Outcomes in Short Stem Total Hip Arthroplasty - Tippimanchai, Thanut; Suksathien, Yingyong; Suksathien, Rachawan (Journal of Southeast Asian Orthopaedics, 2022)
Background: Many previous studies have shown good clinical and radiographic results with the short stem THA. However, few studies have evaluated patient-reported outcomes with the short stem, which is a very important indicator for assessing the outcome of short stem THA from a patient-centered perspective. Objectives: To evaluate the quality of life, patient satisfaction, patient expectations and fulfilment of expectations after short stem THA. Materials and Methods: Patients who have undergone short stem THA more than 1 year from index surgery were interviewed face-to-face or via telephone. Three questionnaires were used to evaluate patient-reported outcomes including quality of life, patient satisfaction, patient expectations and fulfilment of expectations. Results: There were 142 patients in this study. EQ-VAS and EQ-Index showed a high level of patients’ quality of life postoperatively. 98% of cases were satisfied with the outcome of short stem THA. There were significant correlations between EQ-VAS and EQ-Index with patient satisfaction (r=0.401, p<0.001 and r=0.435, p<0.001 respectively). A total 96.4% of patients had their expectations fulfilled. Patient satisfaction and quality of life were significantly correlated with expectations fulfilled. In multivariate analysis, postoperative LOS more than 5 days, limitation of climbing stairs, quality of life, postoperative complications, according to patients’ view, and patient satisfaction were significantly correlated with the fulfilment of expectations. Conclusions: This study showed a high level of patient’s quality of life postoperatively, high patient satisfaction and high rate of fulfillment of patient expectations after short stem THA.